URGENSI JAMINAN HALAL BAGI MASYARAKAT USAHA MIKRO KECIL MENENGAH SIDENRENG RAPPANG, PROVINSI SULAWESI SELATAN - ASTRINA NUR INAYAH (MALLOMO: Journal of Community Service, 2025)
The problem that occurs is that MSME business actors (Micro Small and Medium Enterprises) do not yet know the flow of making halal certification on the Halal Information System (Si Halal) account. There are many food products circulating from MSMEs but their halal qualities are not yet known. This happens both in the manufacturing process and in the use of materials that contain haram ingredients. This is very disturbing for society, especially Muslims. The aim of implementing this activity is to carry out halal certificate assistance activities for MSME business actors, where the urgency of halal guarantees is carried out to ensure comfort, security and certainty of the availability of halal products for the community. The method used is the counseling and training method. The partners involved in this activity are MSMEs in Sidenreng Rappang, namely Boegis Cake, Sidrap Onion Crackers, Cake and cookies, Jagjahe, SR Donuts. Implementation of activities carried out (1) Training on making NIB (Business Permit Number) on 19 June 2023, (2) Counseling on the Urgency of Halal Guarantees for the Community for Halal MSMEs MSMEs Go International, on 21 June 2023, (3) Training on creating a Si Halal account, on June 21 2023. The result of this activity is the issuance of halal certificates for MSMEs. The conclusion is that the implementation of the activities ran smoothly in collaboration with the Sidenreng Rappang MSMEs. Participants were very enthusiastic in taking part in the activity.